2015
DOI: 10.1093/database/bav019
|View full text |Cite
|
Sign up to set email alerts
|

BioXpress: an integrated RNA-seq-derived gene expression database for pan-cancer analysis

Abstract: BioXpress is a gene expression and cancer association database in which the expression levels are mapped to genes using RNA-seq data obtained from The Cancer Genome Atlas, International Cancer Genome Consortium, Expression Atlas and publications. The BioXpress database includes expression data from 64 cancer types, 6361 patients and 17 469 genes with 9513 of the genes displaying differential expression between tumor and normal samples. In addition to data directly retrieved from RNA-seq data repositories, manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 86 publications
(82 reference statements)
1
63
0
2
Order By: Relevance
“…11). 44 NF-kB has been hailed as a therapeutic target for cancer treatment owing to its ability to modulate inflammatory responses apart from the other major hallmarks of cancer. 18,45,46 The modulation of IL-4 and IL-8 by GNL3L could promote NF-kB-mediated inflammation in addition to its anti-apoptotic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11). 44 NF-kB has been hailed as a therapeutic target for cancer treatment owing to its ability to modulate inflammatory responses apart from the other major hallmarks of cancer. 18,45,46 The modulation of IL-4 and IL-8 by GNL3L could promote NF-kB-mediated inflammation in addition to its anti-apoptotic function.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-Seq data of 920 pairs of tumor were compared with those of normal tissue samples, which are available in the BioXpress database 44 …”
Section: Gene Expression Profiling From Datasetmentioning
confidence: 99%
“…We found that the levels of miR-3127 in BCA samples were significantly lower than those in the normal samples ( Figure 1C). We also analyzed RNA-sequencing gene expression data of BCA samples and normal samples, which are available in the BioXpress database (Wan et al, 2015). The results suggested that miR-3127 expression was reduced in multiple cancer types including BCA ( Figure 1D).…”
Section: Mir-3127 Expression Is Downregulated In Human Bca Tissues Anmentioning
confidence: 99%
“…To facilitate research on abnormal gene expression in human diseases, a variety of databases and pipelines have been developed to combine RNA-seq from different studies [3][4][5][6][7][8][9][20]. However, these databases or pipelines either directly incorporated expression data from the literature, retaining unwanted batch effects in the data [7][8], or only combined and reanalyzed samples from smaller studies, hence, not taking advantage of the power provided by the recent large data sets [3][4][5][6][20]. A recently published pipeline, Toil [10], attempts to unify RNA-seq data from different sources by uniformly processing raw sequencing reads.…”
Section: Introductionmentioning
confidence: 99%